Toddlers Using Tablets: They Engage, Play, and Learn - Courage, Mary L.; Frizzell, Lynn M.; Walsh, Colin S.; Smith, Megan (Frontiers in Psychology, 2021)
Very young children have unprecedented access to mobile touchscreen devices. Unlike traditional video, these devices enable interactive participation as children engage directly with app content that can be tailored to their interests and skills. Preschoolers older than about three years can use touchscreens to learn new words and concepts, imitate, and solve problems. For younger children, their greater cognitive, fine motor, and attentional immaturities might make this more difficult. To evaluate this, 30 2-yr-olds were compared with 30 3-yr-olds on two commercially available, tablet-based activities: (1) a shape matching puzzle played on successive days, and (2) a storybook reading in which retention of story information was compared after reading from an e-book and a matched paper book. Children also completed the Minnesota Executive Functioning Scale. Executive functions might predict successful learning with interactive devices as they enable children to keep more information in mind, sustain their attention on a task, and resist distraction. The results showed: (1) after controlling for prior experience with shape puzzles, toddlers' skill in using the app improved over the three trials: they increased success and efficiency, made fewer errors, decreased completion times, and required less adult scaffolding, (2) they recognized more story content from the e-book and were less distracted during that reading compared to the paper book, (3) the 3-yr-olds outperformed the 2-yr-olds on both app activities, and (4) children's executive functioning contributed significant and unique variance to the outcome measures on both the shape matching and storybook tasks. The results are discussed in terms of the potential of interactive devices to support learning in toddlers.